Next-generation data center energy management: a data-driven decision-making framework - Milić, Vlatko (Frontiers in Energy Research, 2024)
In the era of society's ongoing digitization and the exponential growth in data volume, alongside a growing energy demand, energy management plays an integral role in the data center (DC) and is a key factor in the quest for decarbonization. In light of the complex nature of DCs, traditional energy management strategies are inadequate. This research introduces a data-driven decision-making framework for DCs, grounded in the OODA (Observation, Orientation, Decision, and Action) loop and based on insights from an Ericsson-operated DC in Linköping, Sweden. The developed framework enables data centers (DCs) to enhance energy efficiency effectively. Rooted in the OODA loop and leveraging extensive datasets from DCs' building management systems, this framework aids in decreasing cooling energy usage through strategic, data-driven decision-making. By adopting AI methods, specifically K-means clustering in this research, for continuous monitoring and fine-tuning (Proportional, Integral, Derivative) PID parameters, the framework aids in improving operational efficiency.